An in Vitro Biosynthesis of Sesquiterpenes Starting from Acetic Acid. (18th October 2018) - Dirkmann, Michael; Nowack, Julia; Schulz, Frank
Abstract: The enzymatic synthesis of terpenes was investigated by using a cascade based on the mevalonic acid pathway. Suitable enzymes from all kingdoms of life were identified and combined to give rise to geosmin and patchoulol as representative compounds. The pathway was studied in three separate segments, which were subsequently combined in a ten‐step cascade plus added cofactor regeneration systems. The cascade delivers farnesyl pyrophosphate with >40 % conversion and cyclises it to sesquiterpenes with >90 % conversion. Abstract : Capturing a catalytic cascade : A biocatalytic cascade from acetate to sesquiterpenes is optimised to access geosmin and patchoulol as model compounds. The pathway has been studied in three separate segments, which are subsequently combined in a ten‐step cascade plus added cofactor regeneration systems.